Apakah Manajemen Risiko Berpengaruh Terhadap Kinerja Bank? - Julia Renaldi, Angelina; Candy, Candy; Yuwono, Wisnu (Distribusi - Journal of Management and Business, 2024)
The objective of this research is to analyze the impact of risk management on bank performance. Risk management is measured through credit risk, liquidity risk, operational risk, leverage, loan growth, and bank capital. Meanwhile, bank performance is measured through ROA (return on assets) and ROE (return on equity). The sample in this study consists of Rural Banks (BPR) in the province of West Kalimantan. Data were collected from the financial statements for the years 2018 until 2022 available on the Financial Services Authority (OJK) website. According to OJK data, there are 21 BPR’s in West Kalimantan resulting in a total of 105 data points used in this study. The analytical method applied is panel regression, tested using the E-Views application. The results show that credit risk, liquidity risk, and operational risk have a negative effect on ROA, while leverage and bank capital have a positive effect on ROA. In contrast, loan growth does not affect ROA. Additionally, credit risk, leverage, operational risk, and bank capital have a negative impact on ROE, whereas liquidity risk and credit growth do not affect ROE.